Abscisic acid alleviates the deleterious effects of cold stress on 'Sultana' grapevine (Vitis vinifera L.) plants by improving the anti-oxidant activity and photosynthetic capacity of leaves. Issue 4 (3rd July 2016) - Karimi, Rouhollah; Ershadi, Ahmad; Rezaei Nejad, Abdolhossein; Khanizadeh, Shahrokh
ABSTRACT: The effects of exogenous application of abscisic acid (ABA) on anti-oxidant enzyme activities and photosynthetic capacity in 'Sultana' grapevine ( Vitis vinifera L.) were investigated under cold stress. When vines had an average of 15 leaves, 0 (control), 50, 100, or 200 µM ABA was sprayed to run-off on all leaves of each plant. Twenty-four hours after foliar spraying with ABA, half ( n = 5) of the water-only control vines and half ( n = 5) of each group of ABA-treated plants were subjected to 4°C for 12 h, followed by a recovery period of 3 d under greenhouse conditions (25°/18°C day/night). The remaining plants in each treatment group were kept at 24°C. Cold stress increased H2 O2 and malondialdehyde (MDA) concentrations in vine leaves, whereas all foliar ABA treatments significantly reduced their levels. Chilled plants showed marked increases in their total soluble protein contents in response to each ABA treatment. ABA significantly increased the activities of superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase in cold-stressed grapevine leaves. In contrast, cold stress markedly decreased the rates of leaf photosynthesis ( A ) and evaporation ( E ), stomatal conductance ( g s ), and chlorophyll concentrations in leaves, but increased intercellular CO2 concentrations ( C i ) in leaves. Treatment with all concentrations of ABA resulted in lower leaf A, E, and g s values, but higher C i values at 24°C. However, following cold stress, ABA-treated vines showed higher leaf A, E, and g s values, but lower C i values compared to control vines without ABA treatment. The application of 50–200 µM ABA allowed chilled vines to recover more quickly when re-exposed to normal temperatures, enabling the vines to resume their photosynthetic capacity more efficiently following cold stress. These results showed that, by stimulating anti-oxidant enzyme systems and alleviating cold-induced stomatal limitations, ABA reduced the inhibitory effect of cold stress on the rate of CO2 fixation in 'Sultana' grapevine plants.